2023
DOI: 10.1021/acs.jafc.3c03930
|View full text |Cite
|
Sign up to set email alerts
|

Protein Phosphorylation Induced by Pyruvate Kinase M2 Inhibited Myofibrillar Protein Degradation in Post-Mortem Muscle

Chi Ren,
Xubo Song,
Yu Dong
et al.

Abstract: Myofibrillar protein degradation is primarily related to meat tenderness through protein phosphorylation regulation. Pyruvate kinase M2 (PKM2), a glycolytic rate-limiting enzyme, is also regarded as a protein kinase to catalyze phosphorylation. The objective of this study was to investigate the relationship between myofibrillar protein degradation and phosphorylation induced by PKM2. Myofibrillar proteins were incubated with PKM2 at 4, 25, and 37 °C. The global phosphorylation level of myofibrillar proteins in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…However, PKM can also transfer the phosphate group from PEP to a protein substrate and act as a protein kinase . PKM inhibits myofibrillar protein degradation by phosphorylation which will regulate meat tenderization . There are more than 900 protein substrates of PKM, suggesting a wide effect of PKM on phosphorylating proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, PKM can also transfer the phosphate group from PEP to a protein substrate and act as a protein kinase . PKM inhibits myofibrillar protein degradation by phosphorylation which will regulate meat tenderization . There are more than 900 protein substrates of PKM, suggesting a wide effect of PKM on phosphorylating proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The previous study showed that actin was one of the phosphorylated substrates of PKM, therefore the kinase assay on actin was performed to evaluate PKM kinase activity . The wtPKM and mutated PKMs were incubated with actin (Shanghai Yuanye Bio-Technology Co., Ltd., Shanghai, China) at 37 °C for 0.5 and 6 h in a buffer consisting of 100 mM KCl, 50 mM MgCl 2 , 1 mM DTT, 1 mM NaVO 4 , 5% glycerin, 2 mM PEP, 30 mM HEPES, pH 7.5.…”
Section: Methodsmentioning
confidence: 99%